Enhancing the functionality of the Audiovisual Studio Education Laboratory in developing Broadcasting competencies for communication science students at Universitas Ahmad Dahlan - Supriadi, Bambang (Universitas Ahmad Dahlan, 2024)
The structured and measurable management of an Audiovisual Studio laboratory plays a critical role in developing scientific competence in Audio Visual production. This study aims to examine the enhancing the functionality of the Audiovisual Studio Education Laboratory in developing broadcasting competencies for communication science students at Universitas Ahmad Dahlan. In an evolving media landscape characterized by rapid information flow, the laboratory serves as a crucial facility for preparing students to meet the demands of the dynamic media industry. Using qualitative research methods, this study involves direct observation, literature review, field analysis, and document analysis related to curriculum and laboratory activities. The findings reveal that the Audiovisual Studio education laboratory holds significant potential as an effective learning center, fostering technical, creative, and analytical skills in media production. However, challenges remain, including outdated facilities, the need for integration of advanced technologies, limited industry collaboration, and the necessity for a curriculum aligned with industry standards. This research provides insights into the practices and challenges of optimizing the laboratory's role and offers recommendations for UAD and other institutions to enhance broadcasting education. Ultimately, the study contributes to preparing students as competent broadcasting professionals equipped to thrive in the current and future media industry.